1997
DOI: 10.1007/bf02445094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiation from personal computer monitor on free-radical processes in rats

Abstract: Radiation from a personal computer monitor reduces antioxidant activity and the contents of diene conjugates and Schiff bases in rat serum and has no effect on chemiluminescence and the content of carbonyl derivatives. The radiation causes no significant changes in blood contents of nitrites and ceruloplasmin and activity of Cu,Zn-superoxide disnmtase. The results obtained indicate that radiation from a monitor produces potentially hazardous biological effects. Key Words: monitor; lipid peroxidation; antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A personal computer (PC) is standard equipment for many people in industrialized societies, and its use is growing. A PC user is exposed to an electromagnetic field (EMF), visible and ultraviolet light, radio-range waves, and extremely low frequency (50 Hz) fields (ELF) [2]. Preliminary experiments showed that radiation from a monitor can produce potentially hazardous biological effects [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A personal computer (PC) is standard equipment for many people in industrialized societies, and its use is growing. A PC user is exposed to an electromagnetic field (EMF), visible and ultraviolet light, radio-range waves, and extremely low frequency (50 Hz) fields (ELF) [2]. Preliminary experiments showed that radiation from a monitor can produce potentially hazardous biological effects [2].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that ELF-EMFs may interfere with chemical reactions involving free radical production [12-14]. Moreover, some researchers have reported that PC monitor use is associated with the free radical process [2,15]. The eye is an exceptional organ because of its continuous exposure to environmental chemicals, radiation, and atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 99%